The nucleoid-associated protein HU controls three regulons that coordinate virulence, response to stress and general physiology in Salmonella enterica serovar Typhimurium - DORMAN, CHARLES; HINTON, JAY (My University, 2011)
The role of the HU nucleoid-associated proteins in gene regulation was examined in Salmonella enterica serovar Typhimurium. The dimeric HU protein consists of different combinations of its ? and ? subunits. Transcriptomic analysis was performed with cultures growing at 37?C at 1, 4 and 6 hours post-inoculation with mutants that lack combinations of HU ? and HU ?. Distinct but overlapping patterns of gene expression were detected at each time point for each of the three mutants, revealing not one but three regulons of genes controlled by the HU proteins. Mutations in the hup genes altered the expression of regulatory and structural genes in both the SPI1 and the SPI2 pathogenicity islands. The hupA hupB double mutant was defective in invasion of epithelial cell lines and in its ability to survive in macrophages. The double mutant also had defective swarming activity and a competitive fitness disadvantage compared to the wild type. In contrast, inactivation of just the hupB gene resulted in increased fitness and correlated with the up-regulation of members of the RpoS regulon in exponential phase cultures. Our data show that HU coordinates the expression of genes involved in central metabolism and virulence genes, and contributes to the success of S. enterica as a pathogen.
PUBLISHED
Published online 06 January 2011
Keywords: Genetics; Infection; Typhimurium; Genes & Society; Immunology, Inflammation & Infection